STRATEGI GURU DALAM MENUMBUHKAN JIWA KEWIRAUSAHAAN SISWA MELALUI PROGRAM UNGGULAN MARKET DAY (MEMBUAT BUNGA DARI KRESEK) DI SDN 050/VI LUBUK MENTILIN - andriani, andriani; Misnawati, Ledia; Agrita, Tri Wera (Jurnal Pendidikan Vokasi dan Seni, 2025)
This study aims to analyze teacher strategies in fostering students' entrepreneurial spirit through the Market Day flagship program with activities to make flowers from plastic bags at SDN 050/VI Lubuk Mentilin. The research method used is qualitative descriptive with data collection techniques through observation, interviews, and documentation. The subjects of the study consisted of the principal, the teacher coordinating the Market Day program, and students in grades IV-VI. The results of the study indicate that teacher strategies in fostering students' entrepreneurial spirit include: (1) integrated program planning, (2) coaching skills in making flowers from plastic bags, (3) implementing Market Day periodically, (4) mentoring the production process to marketing, and (5) continuous reflective evaluation. The Market Day program has proven effective in fostering entrepreneurial values such as creativity, independence, self-confidence, cooperation, responsibility, and communication skills. In addition to being economically and educationally beneficial, this program also contributes to the utilization of plastic waste into valuable products. This study provides an overview that entrepreneurship education can be implemented effectively through a structured program that integrates entrepreneurial values, practical skills, and environmental awareness since elementary education.